Basophils in the giant papillae of chronic allergic keratoconjunctivitis. Issue 4 (14th October 2009) - Matsuda, A; Ebihara, N; Yokoi, N; Okayama, Y; Watanabe, Y; Kawasaki, S; Tanioka, H; Walls, A F; Hamuro, J; Kinoshita, S; Murakami, A
Abstract : Aims: The essential role of basophils as an initiator of chronic allergic reaction has been elucidated in mouse models. The aim of this present study was to analyse the in situ immunolocalisation of basophils and other relevant inflammatory cells in chronic allergic keratoconjunctivitis. Methods: Transmission electron microscopic (TEM) analysis was carried out to examine the existence of basophils in the giant papillae obtained from atopic keratoconjunctivitis (AKC) and vernal keratoconjunctivitis (VKC) patients. Cryostat sections of giant papillae were immunostained with basophil-specific antibody BB-1, and with anti-CD4, anti-CD8, anti-CD20, anti-major basic protein (MBP), anti-IgE and anti-FcɛRI-β antibodies. Results: TEM analysis confirmed the existence of basophils in the giant papillae. Small clusters of basophils were observed in the substantia propria of giant papillae, especially at the vicinity of vascular endothelium and subepithelial regions. BB-1-positive basophil clusters were surrounded by T cells, B cells, IgE-positive cells and MBP-positive eosinophils. No BB-1-positive basophils were observed in the control conjunctivae. Conclusion: Basophils may infiltrate from either vascular endothelium into the giant papillae. The existence of basophils at the centre of inflammatory cells suggests the role of basophils as an initiator of chronic allergic conjunctivitis.